Preoperative Pulmonary Function Testing to Predict Recurrence of Chronic Rhinosinusitis With Nasal Polyps. (July 2020) - Nakamaru, Yuji; Suzuki, Masanobu; Honma, Aya; Nakazono, Akira; Kimura, Shogo; Fujiwara, Keishi; Morita, Shinya; Konno, Satoshi; Homma, Akihiro
Background: Although the close relationship between the upper and lower airways has been highlighted previously, little is known about the association between lung function and the recurrence of chronic rhinosinusitis with nasal polyps (CRSwNP). This study aimed to evaluate the factors associated with pulmonary function that affect CRSwNP recurrence after surgery. Methods: We performed a series of routine pulmonary function tests for general anesthesia prior to CRSwNP surgery. The values for each parameter were compared in the presence or absence of recurrence. Results: Sixty-nine patients with CRSwNP were included. The percent predicted forced expiratory volume in one second (%FEV1 ) in the recurrent group was significantly lower than that in the non-recurrent group ( P = .005). A multivariable logistic regression model revealed that %FEV1 was a positive predictor of recurrence (odds ratio: 0.96, 95% CI: 0.92-0.99, P = .023). There were no significant differences in the other pulmonary functions between the two groups. Conclusions: We found that %FEV1 may be a predictor of CRSwNP recurrence after surgery. As %FEV1 is a pulmonary function test that is routinely performed before surgery, this parameter is readily applicable. Moreover, as %FEV1 appears to have the potential to reveal concealed asthma, %FEV1 might be a particularly useful tool for the prediction of CRSwNP recurrence after surgery.